Respon Pemberian Jenis Pupuk Organik terhadap Hasil Jagung Manis (Zea mays saccharata Sturt) di Lahan Podsolik Merah Kuning - Paridawati, Ika; Karenina, Tili; Amir, Nurbaiti; Palmasari, Berliana; Sofian, Ahmad; Yansi, Ihsan Febri (Publikasi Penelitian Terapan dan Kebijakan, 2023)
The use of organic fertilizers can increase soil fertility and improve the physical, chemical and biological of the soil. The study aimed to determine the best effect and dose of organic fertilizers on yield of sweet corn (Zea mays saccharata Sturt). This research was conducted on Palembang City from Juli to September 2021. This study used an experimental method with a Randomized Block Design (RAK) consisting of 4 treatments and 5 replications. The factors us: Type of Organic Fertilizer (P), namely P0 = Organic Fertilizer Plus Lubricating Oil 750 kg ha-1, P1 = Chicken Manure 20 tons ha-1, P2 = Rice Straw Compost Fertilizer 10 tons ha-1, P3 = Blotong Fertilizer 5 tons ha-1 Observational variables in this study included length of cob (cm), diameter of cob (cm), weight of cob per plant (g) and weight of cob per plot (kg). The results of diversity showed that the treatment of chicken manure 20 tons/ha gave the highest yield of sweet corn at 3.42 kg per plot equivalent to 6.84 tons ha-1. Organic fertilizers can be used to reduce the use of inorganic fertilizers in plant cultivation.